Asylum seekers in the Finnish football clubs : case study of the opportunities and challenges in the collaboration - Goncharenko, Nikita (2019)
The study refers to the social need of Finnish football clubs in learning how to collaborate with culturally distant asylum seekers from the Middle East. The recent influx of 30.000 asylum seekers happened in Finland, in 2015. Many of these asylum seekers intend to stay in Finland on a permanent basis. At the same time, the large number of asylum seekers from the Middle East possess a high interest in football. Finnish football clubs, obtaining a constant need in volunteers, start recruiting asylum seekers, as volunteers. However, there appears to be a gap in literature detailing the collaboration between football clubs and asylum seeker volunteers. The main aim of this paper is to interpret reasons for engaging into a collaboration, describing benefits and challenges arising from it. In order to reach the main aim of this study, 9 theme interviews have been conducted with 5 representatives of Finnish football clubs and 4 volunteers with asylum seekers background. As the result of content analysis, seven inductive categories have been created. Results of the study indicated reasons for football clubs (e.g. lack of volunteers), for asylum seekers (e.g. internal motivation to play), and common reasons (e.g. spare energy usage / consumption). In addition, results proclaim the main benefit for asylum seekers being the social integration, while football clubs receive the opportunities of utilizing football academy background and young age of asylum seekers, covering costs through potential governmental grant, and growing popularity through asylum seekers’ community attraction. The downside of the collaboration is that football clubs constantly need to offer asylum seekers the supervision, while asylum seekers might experience loneliness, cultural shock, injuries, as well as prioritize other issues in life and experience certain unrealistic expectations from football clubs. The identification of reasons, benefits and challenges demonstrates that football clubs might be lacking the competence and volunteers for mentoring asylum seekers, which promotes poor social integration and might even lead to the end of collaboration. In such context, the role of Manager of Reception Centre becomes central, as he mediates expectations of football clubs to asylum seekers, helping them to learn and integrate in Finnish culture. As the result, the team commitment of asylum seekers enhances, promoting rather mutually beneficial than challenging collaboration. Such collaboration can be seen as worthful for both parties.